Boundary layer flow adjacent to a vertical plate with constant surface temperature - Anuar Ishak, (Universiti Kebangsaan Malaysia, 2010)
The development of velocity and thermal boundary layers induced by a free stream adjacent to a vertical plate with constant surface temperature was studied. The governing partial differential equations were reduced to ordinary ones by a similarity transformation, before being solved numerically. Both assisting and opposing flows were considered. It was found that the solution was unique for the assisting flow, while dual solutions were found to exist for the opposing flow. The heat transfer rate at the surface was found to increase with both the buoyancy force and the Prandtl number.